Investigating significant health trends in progressive fibrosing interstitial lung disease (INSIGHTS-ILD): rationale, aims and design of a nationwide prospective registry - Behr, Jürgen; Bonella, Francesco; Günther, Andreas; Koschel, Dirk; Prasse, Antje; Pittrow, David; Klotsche, Jens; Kreuter, Michael (BMC pulmonary medicine, 2023)
The progressive course of pulmonary fibrosis (PPF) is observed with variable prevalence in different entities of fibrosing interstitial lung disease (fILD). PPF is characterised by worsening respiratory symptoms, declining lung function and increasing extent of fibrosis on high-resolution computer tomography. In Germany, data are limited on the characteristics and management of such patients.